2021
DOI: 10.1002/cam4.3915
|View full text |Cite
|
Sign up to set email alerts
|

The debatable presence of PIWI‐interacting RNAs in invasive breast cancer

Abstract: Numerous factors influence breast cancer (BC) prognosis, thus complicating the prediction of outcome. By identifying biomarkers that would distinguish the cases with poorer response to therapy already at the time of diagnosis, the rate of survival could be improved. Lately, Piwi‐interacting RNAs (piRNAs) have been introduced as potential cancer biomarkers, however, due to the recently raised challenges in piRNA annotations, further evaluation of piRNAs’ involvement in cancer is required. We performed small RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Those aberrantly expressed piRNAs in breast cancer including piR-4987, piR-021285, piR-823, piR-932, piR-36712, piR-016658 and piR-016975 may held potential to be developed as biomarkers and/or therapeutic targets in breast cancer. Our recent study also identified 415 piRNA sequences from the medium of luminal subtype of human breast cancer cell MCF-7, in which 27 piRNAs showed deregulation by prooncogene cyclin D1 (28) (51). Three small RNAs annotated as piRNA database entries (DQ596932, DQ570994, and DQ571955) were detected in the tumor samples, all showing upregulation in grade III tumors.…”
Section: Pirnas In Breast Cancermentioning
confidence: 86%
See 1 more Smart Citation
“…Those aberrantly expressed piRNAs in breast cancer including piR-4987, piR-021285, piR-823, piR-932, piR-36712, piR-016658 and piR-016975 may held potential to be developed as biomarkers and/or therapeutic targets in breast cancer. Our recent study also identified 415 piRNA sequences from the medium of luminal subtype of human breast cancer cell MCF-7, in which 27 piRNAs showed deregulation by prooncogene cyclin D1 (28) (51). Three small RNAs annotated as piRNA database entries (DQ596932, DQ570994, and DQ571955) were detected in the tumor samples, all showing upregulation in grade III tumors.…”
Section: Pirnas In Breast Cancermentioning
confidence: 86%
“…Furthermore, patients with estrogen receptor positive and DQ571955 high had shorter relapse-free survival, suggesting DQ571955 as a potential marker for predicting radiotherapy response in estrogen receptor positive breast cancer. In addition, DQ570994 showed potential for predicting tamoxifen and chemotherapy response (51). In triple negative breast cancer (TNBC), neoadjuvant chemotherapy (NACT) is increasingly applied to the therapy management due to its positive association with response rates of patients.…”
Section: Pirnas In Breast Cancermentioning
confidence: 99%
“…DQ570994 was a candidate predictive marker for tamoxifen and chemotherapy response. Overall, these three small RNAs have their own values as biomarkers for BC [ 72 ]. Haug et al investigated the prognostic value of the mRNA-miRNA-lncRNA network in TNBC using the GEO2R tool.…”
Section: Clinical Value Of Non-coding Rnas In Bcmentioning
confidence: 99%
“…A study by Kärkkäinen et al. found that lncRNAs are involved in the signalling pathways of breast cancer [89] . Flores-Huerta et al.…”
Section: Role Of Ncrnas In Breast Cancersmentioning
confidence: 99%